LC-MS/MS based metabolite profiling and lipase enzyme inhibitory activity of Kaempferia angustifolia Rosc. with different extracting solvents - Mohamad Rafi; Alfi Hudatul Karomah; Dewi Anggraini Septaningsih; Trivadila; Min Rahminiwati; Sastia Prama Putri; Dyah Iswantini (Arabian Journal of Chemistry, 2022)
Kaempferia angustifolia also known as kunci pepet in Indonesia, has been widely used as a traditional medicine to treat cold, cough, stomachache, diarrhea, fever, and dysentery, also used as a slimming agent. The level of biological activity depends on the composition and concentration of bioactive compounds present in the plants. In addition, extraction solvents affects the composition and concentration of bioactive compounds. Therefore, this study aimed at identifying the metabolite profile of K. angustifolia and to evaluate the inhibitory potential of their various solvent extracts towards lipase enzyme. Extracts were prepared using water and different concentration of ethanol (30–99%) and then analyzed their metabolite profile using LC-MS/MS. Lipase inhibitory activity was assessed using in vitro enzymatic inhibition assay. In this study, profile of K. angustifolia was shown to be rich in terpenoids (monoterpenoids, sesquiterpenoids, diterpenoids), and phenolics (carboxylic acid and phenolic acid). Most of the identified compounds were detected in ethanol extract of K. angustifolia. The ethanol extract at 100 μg/mL displayed 59.82% inhibitory activity towards lipase and was found to have the highest inhibitory activity compared to the other extracts. A partial least square-discriminant analysis (PLS-DA) was performed for clustering the extracts based on the peak area of 53 putatively identified compounds. Based on the result obtained, 50% ethanol extract is the best extract that gives the highest inhibition results and 15 metabolites were identified, mainly from the carboxylic acid and terpenoid groups.